Later age at menopause was associated with higher cognitive function in post-menopausal women - Rachmiyani, Irmiya; Surjadi, Lily Marliany; Nirmalasari, Rully Ayu; Imran, Yudhisman (Faculty of Medicine, Trisakti University, 2018)
BACKGROUND Menopause is a condition in which the menstrual periods have stopped for the last 12 months due to cessation of ovarial functions causing estrogen hormones to decrease. Various studies find that many factors affect cognitive function at post-menopausal age among others the decrease in estrogens, age at menopause, duration of menopause, and education. However, the effects have been subject to controversy. The aim of this study was to determine the relationship of age, age at menopause, estradiol level, and education with cognitive function among healthy post-menopausal women. METHODS A cross-sectional study was conducted involving 31 post-menopausal women between 50 to 75 years old. Data on age, age at menopause, and education were collected using a questionnaire. The estradiol levels were measured using an electrochemiluminescent immunoassay (ECLIA). The Indonesian version of the Montreal Cognitive Assessment (MoCA INA) was used to assess the cognitive function. Multiple linear regression was used to analyze the data. A p<0.05 was considered statistically significant.RESULTS Age (b=-0.086; 95% C.I.=-0.263-0.090; p=324) and estradiol levels (b=0.106; 95% C.I.=-0.018 -0.230; p=0.092) were not significantly associated with cognitive function. However, education (b=1.537; 95% C.I.=0.176-2.898; p=0.028) and age at menopause (b=0.364;0.056-0.671; p=0.022) were significantly associated with cognitive function. Age at menopause was the most influential factor of cognitive function (Beta=0.402) compared to education (Beta=0.394).CONCLUSION Later age at menopause could increase cognitive function in post-menopausal women. Our findings are that modifiable factors that delay age at menopause should receive attention, in order to promote cognitive function. Keywords: Age at menopause, estrogens, cognitive function, post-menopausal women